An overview of proactive monitoring and management of respiratory issues in ataxia-telangiectasia in a specialist and shared care pediatric clinic - Bhatt, Jayesh Mahendra; Bush, Andrew (Frontiers in Pediatrics, 2024)
Ataxia-telangiectasia (A-T) is an ultrarare autosomal recessive disorder and occurs in all racial and ethnic backgrounds. Clinically, children and young people with A-T are affected by sinopulmonary infections, neurological deterioration with concomitant bulbar dysfunction, increased sensitivity to ionizing radiation, immunodeficiency, a decline in lung function, chronic liver disease, endocrine abnormalities, cutaneous and deep-organ granulomatosis, and early death. Pulmonary complications become more frequent in the second decade of life and are a leading cause of death in individuals with A-T. Oropharyngeal dysphagia is common, progressive, and a risk factor for frequent respiratory infections. Immunodeficiency is non-progressive in most patients with A-T. If severe infections occur, one should be aware of other possible causes, such as aspiration. We provide an overview of current best practice recommendations, which are based on combinations of extrapolation from other diseases and expert opinion. These include proactive surveillance, monitoring, and early management to improve lung health in this devastating multisystem disease.